Active control in flexible plates with piezoelectric actuators using linear matrix inequalities - Bueno, Douglas Domingues [UNESP]; Marqui, Clayton Rodrigo [UNESP]; Lopes Jr., Vicente [UNESP] (My University, 2006)
The study of algorithms for active vibrations control in flexible structures became an area of enormous interest, mainly due to the countless demands of an optimal performance of mechanical systems as aircraft, aerospace and automotive structures. Smart structures, formed by a structure base, coupled with piezoelectric actuators and sensor are capable to guarantee the conditions demanded through the application of several types of controllers. The actuator/sensor materials are composed by piezoelectric ceramic (PZT - Lead Zirconate Titanate), commonly used as distributed actuators, and piezoelectric plastic films (PVDF-PolyVinyliDeno Floride), highly indicated for distributed sensors. The design process of such system encompasses three main phases: structural design; optimal placement of sensor/actuator (PVDF and PZT); and controller design. Consequently, for optimal design purposes, the structure, the sensor/actuator placement and the controller have to be considered simultaneously. This article addresses the optimal placement of actuators and sensors for design of controller for vibration attenuation in a flexible plate. Techniques involving linear matrix inequalities (LMI) to solve the Riccati's equation are used. The controller's gain is calculated using the linear quadratic regulator (LQR). The major advantage of LMI design is to enable specifications such as stability degree requirements, decay rate, input force limitation in the actuators and output peak bounder. It is also possible to assume that the model parameters involve uncertainties. LMI is a very useful tool for problems with constraints, where the parameters vary in a range of values. Once formulated in terms of LMI a problem can be solved efficiently by convex optimization algorithms.
Keywords: Actuators and sensors; Automotive structures; Convex optimization algorithms; Lead zirconate titanate; Linear quadratic regulator; Optimal placement of sensors; Piezoelectric actuators and sensors; Vibration attenuation; Aircraft control; Algorithms; Convex optimization; Decay (organic); Flexible structures; Linear matrix inequalities; Optimization; Piezoelectric ceramics; Plates (structural components); Semiconducting lead compounds; Sensors; Structural design; Vibrations (mechanical); Piezoelectric actuators